THE DEVELOPMENT OF NUMBER OF OBJECTS COUNTING ON DIGITAL IMAGE APPLICATION BY USING MATHEMATICAL MORPHOLOGY METHOD AND CONNECTED COMPONENT LABELING TECHNIQUE - I Komang Deny Supanji (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research aimed to design and develop an application that can be used to count the number of objects in digital image by using mathematical morphology method and connected component labeling technique. The input and output from this application is a bitmap type image. The implementation of mathematical morphology method and connected component labeling technique on this application produces an application called CITRAcounter developed by using Borland Delphi 7 programming language. This application is able to process the RGB image, grayscale image and binary image. CITRAcounter has three main processes, those processes are : the binary process, morphology, and labeling. The definition of objects on this research are regions in image that are white. For the image of objects which have simple shapes, the counting result is very accurate. However, for the image of objects which have accumulated position will produce inaccurate counting result.